2019
DOI: 10.3389/fneur.2019.01146
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carotid Intraplaque Neovascularization Using Superb Microvascular Imaging in High Risk of Stroke Individuals: Results From a Community-Based Study

Abstract: Background: Improved stroke risk stratification may improve stroke prevention. We aimed to study the value of a novel Doppler method, superb microvascular imaging (SMI), in correlating plaque thickness and evidence of intra-plaque neovascularization with a history stroke and TIA involving any cerebrovascular territory among community residents considered at high stroke risk.Methods: We selected residents aged at least 40 years from the Donghuashi community in China who had at least three stroke risk factors (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Wang et al conducted a study in a population of 131 individuals at high stroke risk. Subjects with moderate or marked neovascularization as measured by SMI were more significantly more likely to have a history of stroke or transient ischemic attack [72]. SMI and CEUS have been shown to have good consistency in detecting neovascularization.…”
Section: Superb Microvascular Imagingmentioning
confidence: 95%
“…Wang et al conducted a study in a population of 131 individuals at high stroke risk. Subjects with moderate or marked neovascularization as measured by SMI were more significantly more likely to have a history of stroke or transient ischemic attack [72]. SMI and CEUS have been shown to have good consistency in detecting neovascularization.…”
Section: Superb Microvascular Imagingmentioning
confidence: 95%
“…Preferred reporting items for systematic reviews and meta-analyses (PRISMA) flow diagram shown in Figure 1, which demonstrates that a total of 95 reports were analyzed in the systematic search, 11 studies of which were met all inclusion criteria and included in our meta-analysis. 5,6,[8][9][10][12][13][14][15][16][17] The research population consisted of 605 patients (mean age, 66 years) and all patients had carotid stenosis >50% or carotid plaque thickness > 1.5 mm. We summarized the study characteristics in Table 1 and the methodological difference in Table 2.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…While 4 studies reported the consistency of SMI in detecting IPN and pathologic evaluations of IPN. 5,9,14,17 The pooled summary correlation Canon Aplio500, L7.5 1.5 Canon Aplio500, L7.5 0.12 Sonovue 2.5 ml Wang et al 6 Canon Aplio500, L7.5 1.5 NA NA NA NA Zhu et al 12 Toshiba Aplio500, L7.5 NA Toshiba Aplio500, L7.5 NA SonoVue 4 ml Xie et al 13 Toshiba Aplio500, L7.5 NA Toshiba Aplio500, L7.5 NA Sonovue 1.2 ml Oura et al 10 Toshiba Aplio500, L7.5 1.5 Toshiba Aplio500, L7.5 0.19-0.26 Sonazoid 0.01 ml/kg Zhang et al 16 Toshiba Aplio500, L4-11 coefficient R was 0.52 (95% CI = 0.40-0.62, P = .00) and heterogeneity was I 2 = 20.0% (P = .28, Figure 3). The odds ratio of IPN detected by SMI and history of stroke or TIA was reported in 3 studies.…”
Section: Meta-analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The SMI technique for motion artifact-specific characteristic analysis enables filtering that eliminates only the motion artifact and facilitates visualization of low velocity blood flow [84]. One study showed that moderate to severe intraplaque neovascularization detected by SMI was more prevalent in subjects with a history of stroke or TIA or with thicker plaques [86]. SMI is a promising noninvasive alternative to CEUS for the assessment of carotid plaque stability [87] and may help prevent ischemic stroke (Figure 6a,b) [88].…”
Section: Superb Microvascular Imaging (Smi)mentioning
confidence: 99%